Tác động của công bố thông tin trách nhiệm xã hội đến rủi ro giảm giá cổ phiếu của các công ty niêm yết trên thị trường chứng khoán Việt Nam - Cao Thị Miên, Thùy; Nguyễn Vĩnh, Khương; Nguyễn Thanh, Liêm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The study was conducted to examine the impact of corporate social responsibility disclosure on stock price crash risk of listed companies in Vietnam. Based on data from 225 companies listed on the Vietnamese stock market over the period 2014–2018, the authors use GMM estimator to evaluate the aforementioned nexus. The authors conclude that corporate social responsibility disclosure has a negative effect on stock price crash risk. This paper contributes to the literature on this relationship in developing countries. The authors then give some policy implications on the transparency of social responsibility information disclosure of listed companies and management agencies from research results.